Implicature in Radiohead’s Album OK Computer’s Lyrics - Rahmat, Muhamad Khatami; Fadil, Ahmad Mahesa; Yastanti, Unpris (Universitas Islam Negeri Sunan Gunung Djati, 2025)
This study investigates the use of implicature in the lyrics of Radiohead’s album OK Computer within the broader field of pragmatics, emphasizing how meaning is constructed beyond literal interpretation in artistic discourse. The study aims to identify the types of implicature present in the album and to explain how implied meanings are generated through linguistic choices in song lyrics. Grounded in H. P. Grice’s theory of conversational implicature and the Cooperative Principle, this qualitative research analyzes eight selected songs from OK Computer: “Airbag,” “Paranoid Android,” “Subterranean Homesick Alien,” “Let Down,” “Karma Police,” “No Surprises,” “Climbing Up the Walls,” and “Lucky.” The analysis focuses on the observance and flouting of Grice’s maxims of Quantity, Quality, Relation, and Manner to uncover implicit meanings embedded in the lyrics. The findings reveal a total of 85 implicatures, consisting of 83 conversational implicatures and 2 conventional implicatures, indicating that conversational implicature is the dominant strategy employed throughout the album. Songs such as “Climbing Up the Walls,” “Airbag,” and “Let Down” show a high frequency of implicature, reflecting themes of fear, alienation, technological anxiety, and emotional vulnerability. In conclusion, the study demonstrates that implicature functions as a central pragmatic device in OK Computer, enabling Radiohead to communicate complex emotional and social meanings while maintaining poetic subtlety and interpretive openness.